Psychological distress in siblings of people with mental illness: A systematic review and meta-analysis. (May 2023) - Jayasinghe, Anuradhi; Wrobel, Anna; Filia, Kate; Byrne, Linda K; Melvin, Glenn; Berk, Lesley; Berk, Michael; Cotton, Sue
Objective: The objective of this study was to characterise the prevalence and/or severity of psychological distress (namely, depression and anxiety symptoms) in siblings of people with mental illness (MI) and to examine correlates of distress in siblings of people with MI. Method: Studies comparing distress in individuals with and without a sibling with MI were eligible. Studies reporting on correlates of distress in siblings were also eligible. A search of MEDLINE Complete, PsycINFO and Embase was conducted up until 17 March 2022. Results: Fifteen studies comprising 2304 siblings and 2263 comparison individuals were included. Meta-analyses indicated individuals with a sibling with MI experience significantly greater depressive symptoms (Hedges's g  = 0.53, 95% CI = [0.32, 0.73], siblings n  = 1962, comparison individuals n  = 2248) and anxiety symptoms (Hedges's g  = 0.40, 95% CI = [0.19, 0.61], siblings n  = 653, comparison individuals n  = 533) than those without. The sibling relationship, siblings' locus of control, interpersonal functioning and their appraisal of the impacts of MI were identified as important and potentially modifiable correlates. Conclusion: Individuals with a sibling with MI experience greater depressive and anxiety symptoms than those without and would likely benefit from support. Future studies are required to elucidate the mechanisms underlying distress in siblings.